Evaluating the performance of ReaxFF potentials for sp2 carbon systems (graphene, carbon nanotubes, fullerenes) and a new ReaxFF potential - Fthenakis, Zacharias G.; Petsalakis, Ioannis D.; Tozzini, Valentina; Lathiotakis, Nektarios N. (Frontiers in Chemistry, 2022)
We study the performance of eleven reactive force fields (ReaxFF), which can be used to study sp$^2$ carbon systems. Among them a new hybrid ReaxFF is proposed combining two others and introducing two different types of C atoms. The advantages of that potential are discussed. We analyze the behavior of ReaxFFs with respect to (i) the structural and mechanical properties of graphene, its response to strain and phonon dispersion relation; (ii) the energetics of $(n,0)$ and $(n,n)$ carbon nanotubes (CNTs), their mechanical properties and response to strain up to fracture; (iii) the energetics of the icosahedral C$_{60}$ fullerene and the 40 C$_{40}$ fullerene isomers. Seven of them provide not very realistic predictions for graphene, which made us focusing on the remaining, which provide reasonable results for (i) the structure, energy and phonon band structure of graphene, (ii) the energetics of CNTs versus their diameter and (iii) the energy of C$_{60}$ and the trend of the energy of the C$_{40}$ fullerene isomers versus their pentagon adjacencies, in accordance with density functional theory (DFT) calculations and/or experimental data. Moreover, the predicted fracture strain, ultimate tensile strength and strain values of CNTs are inside the range of experimental values, although overestimated with respect to DFT. However, they underestimate the Young's modulus, overestimate the Poisson's ratio of both graphene and CNTs and they display anomalous behavior of the stress - strain and Poisson's ratio - strain curves, whose origin needs further investigation.